Woman in rape: a victim or a criminal? - Gennadievna, Adeeva Ekaterina Ekaterina (Teisė, 2012)
Postgraduate student of Department of Criminal Law and Penal Law of Tashkent State Law Institute, Uzbekistan E-mail: adeev2005@mail.ru